Soul of a Nation : Art in the Age of Black Power. - Godfrey, Mark; Cahan, E. Susan; Bryant, Linda Goode; Driskell, David, C.; Gaither, Edmund Barry; Jarell Jae en Wadsworth; Lewis, Samella; Whitley, Zoé (Tate Publishing : London, 2017)
Amos, Emma ; Andrews, Benny ; Bearden, Romare ; Bellow, Cleveland ; Bey, Dawoud ; Bowling, Frank ; Brown, Kay ; Catlett, Elizabeth ; Clark, Ed ; Cowans, Adger ; Cowherd, Darryl ; Decarava, Roy ; Donaldson, Jeff ; Douglas, Emory ; Draper, Louis ; Edwards, melvin ; Fennar, Al; Gammon, Reginald ; Gilliam, Sam ; Hammons, David ; Hendricks, Barkley ; Jaramillo Virginia ; Jarell, Jae ; Lawrence, Catherine ; Lewis , Norman; ea.
burgerrechten, black power, black feminism, AfriCOBRA, Black Arts movement
Soul of a Nation: Art in the Age of Black Power, Tate Modern, London, 12 juli-23 april 2017
boek